«Le fjord glacé d’Ilulissat: la mise en tourisme d’un paysage naturel patrimonialisé» - Poiret, Andréa (CEM – Cultura, Espaço & Memória, 2021)
Tourism started slowly in Ilulissat (Greenland) in the 1980s-1990s, before expanding further in the 21st century since the UNESCO classification of the Sermeq Kujalleq Glacier Fjord and the fact that the Arctic has become a symbol of climate change. These journeys are both imaginary, described as «cryotropism», «borealism» or «nordicity», and very real: the impact of tourism is visible in the environment. A new international airport is planned for 2023. What type of tourist and therefore travel will this attract? We asked ourselves to what extent the Ilulissat natural site could be managed in a sustainable way. In order to answer this question, we adopted the participant observation from an immersion in the Ilulissat Fjord Office and conducted about twenty semistructured interviews.